Co-construction and artificial intelligence in teaching management: a case study in Chile - Rojas Bruna, Carlos (2025)
This article originates from a presentation submitted to the XXII Conference on Higher Education Management at the International Education Summit UC, which was expanded through a documentary research process and institutional analysis. It presents a case study on the integration of artificial intelligence (AI) in the teaching management of a university faculty in Chile, characterized by large-scale operations and complex administrative processes. The aim is to describe and analyze an institutional improvement process focused on anticipating, validating, and standardizing critical stages of the teaching cycle through automated and collaboratively developed tools. The study followed a qualitative case study design combining documentary analysis and process observation, integrating evidence from course planning, enrolment, classroom allocation, schedule validation, and assessment verification. A key feature of the case was the participatory work of the teaching management team, which co-designed and implemented AI solutions as part of a broader process of literacy and ethical deliberation on their use. Findings suggest that AI, understood as an administrative co-teacher, can enhance traceability, efficiency, and data-informed decision-making, while fostering a culture of democratic innovation and shared responsibility within university management.